THE INFLUENCE OF STORYNOMICS AND TOURISM PRODUCTS ON TOURIST VISITING INTEREST IN THE RAJA PRAILIU TRADITIONAL VILLAGE, EAST SUMBA REGENCY - Hidayatullah, Syarif; Alvianna, Stella; Ramu Yulia Pandarangga (Ride: Journal of Cultural Tourism and Religious Studies, 2024)
This research aims to analyze the influence of storynomics and tourism products on tourist interest in visiting. The research method used in this research is a quantitative method. The data collection instrument used was a questionnaire. The dependent variable in this research is the visiting interest variable and the independent variables are storynomics and tourism products in the Raja Prailiu Traditional Village, East Sumba district. The results of this research are that there is a positive and significant partial storynomic influence on tourists' interest in visiting the Raja Prailiu Traditional Village in accordance with the existing living culture. Partially, tourism products have a positive and significant effect on tourists' interest in visiting the Raja Prailiu Traditional Village. Tourism products provide a special attraction for tourists interested in visiting the Raja Prailiu Traditional Village. Based on the simultaneous test (F test) which was carried out to test whether or not there was an influence of the independent variables simultaneously on the dependent variable so that in this study storynomics and tourism products simultaneously had a positive effect on tourists' interest in visiting. Based on the results of the regression test which states that the regression coefficient value of the tourism product variable is greater than the storynomic regression coefficient value, it can be concluded that the tourism products in the Raja Prailiu Traditional Village have a dominant influence on tourist interest in visiting the Raja Prailiu Traditional Village.